2015
DOI: 10.1007/s12011-015-0581-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excess Iodine on Oxidative Stress Markers, Steroidogenic—Enzyme Activities, Testicular Morphology, and Functions in Adult Male Rats

Abstract: Improper iodine intake is a major concern in public health. Chronic intake of low iodine affects gonadal functions of man and animals; however, such effects of excess iodine in male reproduction, specially on testicular morphology, testicular steroidogenic enzyme activities, sperm morphology, sperm viability, and sperm count including male hormonal profiles in reference to iodine status and thyroid hormone profiles are yet to be explored. With this background, adult male rats of 120 ± 10 gm Bw of 90 ± 5 days w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…In this investigation the adrenal gland weight was increased following thiourea administration. It was reported previously that such a condition can arise as a result of the stress response, yet it may also occur due to deficient glucocorticoid feedback regulation of ACTH due to toxicity to the adrenal cortex (Chakraborty et al ., 2016). Thus excess thiourea as used in this study might be responsible for producing oxidative stress in the adrenal resulting in the cellular and subcellular alterations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this investigation the adrenal gland weight was increased following thiourea administration. It was reported previously that such a condition can arise as a result of the stress response, yet it may also occur due to deficient glucocorticoid feedback regulation of ACTH due to toxicity to the adrenal cortex (Chakraborty et al ., 2016). Thus excess thiourea as used in this study might be responsible for producing oxidative stress in the adrenal resulting in the cellular and subcellular alterations.…”
Section: Discussionmentioning
confidence: 99%
“…It is a gradual process in which free radicals steal electrons from the lipid in the cell membrane. Malonaldehyde (MDA) levels thus formed indicate the intoxication and generation of oxidative stress in this organ, considered an endpoint of oxidative stress formation (Chakraborty et al ., 2016). This clearly suggests that thiourea exposure caused elevation of LPO level or in other words generation of oxidative stress resulting in adrenal gland weight and subsequent changes in the activity of the gland by feedback mechanism to ACTH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the GO, the upregulated DE genes were involved in the reactive oxygen species activity, oxygen ions and peroxides, lipid peroxidation and so on; the downregulated DE genes were involved in the decrease of immunological ability. All the changes can be caused by oxidative stress, such as cancer suppressor [23], cell normal functions [24], special responses for pathogens [25], maximal actions, and antigen presentation [26] (Figure 6). Pathway analysis revealed that, in intestinal mucosa tissues of participants from high altitude, many pathway genes had aberrant expression and may be also related with oxidative stress, especially in inflammatory bowel diseases [27, 28], myeloperoxidase [29], ROS production [10], apoptotic cell death [30], tissue damage [31], interleukin-1 [32], oxidative modification [33], cystic fibrosis [34], natural killer cells activity [35], lymphocytes [36], fibrinolysis [37] and so on (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on different assortments of sperm analysis are now a recognized methodology in the appraisal of animal semen destined to breeding. Excess iodine induced alterations on male and female reproductive functions have been reported by our group recently; however, its effect on sperm physiology are yet to be explored in details. Further, sperm chromatin structure that interrupt sperm fertility, apoptosis in mature spermatozoa etc under various incremental doses of relatively high iodine and for different durations have not been evaluated earlier.…”
Section: Introductionmentioning
confidence: 96%